An infection cocktail: malaria, dengue, chikungunya and Japanese encephalitis. (January 2019) - Dev, Nishanth
Vector-borne diseases cause a significant burden on healthcare facilities. An increasing number of cases reported with multiple co-infections only add to the ordeal. The presence of co-infection may modify clinical and laboratory parameters significantly making diagnosis and treatment a challenge. Cases of malaria and dengue with other infections such as chikungunya, leptospirosis and hepatitis have been reported previously. We report a case of acute febrile illness with altered sensorium which was eventually diagnosed to have quadruple infection with malaria, dengue, chikungunya and Japanese encephalitis. This may be the first case with four concurrent vector-borne infections, all of which are transmitted by mosquitoes.